Deceiving Communication Links on an Organization Email Corpus - Divya, R.; Kumar, Ch. Aswani; Saijanani, S.; Priyadharshini, M. (Malaysian Journal of Computer Science, 2017)
Word use in email is correlated to the role of the individuals within the organization and relationships among them are based on their patterns of word use. In this paper, using the matrix-decomposition techniques we determine the communication links with individuals who conversed frequently based on their word usage pattern. Further we analyze the emails of all the members of the communication link and isolate the individuals who have surprising results. Later we follow the deception theory, which suggests that deceptive writing is characterized by reduced frequency of first person pronouns, exclusive words, elevated frequency of negative emotion words and action verbs.